2016
DOI: 10.7554/elife.15266
|View full text |Cite
|
Sign up to set email alerts
|

Admixture into and within sub-Saharan Africa

Abstract: Similarity between two individuals in the combination of genetic markers along their chromosomes indicates shared ancestry and can be used to identify historical connections between different population groups due to admixture. We use a genome-wide, haplotype-based, analysis to characterise the structure of genetic diversity and gene-flow in a collection of 48 sub-Saharan African groups. We show that coastal populations experienced an influx of Eurasian haplotypes over the last 7000 years, and that Eastern and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 81 publications
(196 reference statements)
10
124
2
Order By: Relevance
“…Today, some of the earliest branching African lineages are present only in populations with relatively small census sizes, including the southern African Khoe-San (see STAR Methods for terminology), central African rainforest hunter-gatherers, and Hadza of Tanzania (Gronau et al, 2011; Schlebusch et al, 2012; Veeramah et al, 2012). However, the population structure of Africa prior to the expansion of food producers (pastoralists and agriculturalists) remains unknown (Busby et al, 2016; Gurdasani et al, 2015; Patin et al, 2017). Bantu-speaking agriculturalists originating in western Africa are thought to have brought farming to eastern Africa by ~2000 years calBP (calibrated radiocarbon years Before Present, defined by convention as years before 1950 CE) and to southern Africa by ~1500 BP, thereby spreading the largest single ancestry component to African genomes today (Russell et al, 2014; Tishkoff et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Today, some of the earliest branching African lineages are present only in populations with relatively small census sizes, including the southern African Khoe-San (see STAR Methods for terminology), central African rainforest hunter-gatherers, and Hadza of Tanzania (Gronau et al, 2011; Schlebusch et al, 2012; Veeramah et al, 2012). However, the population structure of Africa prior to the expansion of food producers (pastoralists and agriculturalists) remains unknown (Busby et al, 2016; Gurdasani et al, 2015; Patin et al, 2017). Bantu-speaking agriculturalists originating in western Africa are thought to have brought farming to eastern Africa by ~2000 years calBP (calibrated radiocarbon years Before Present, defined by convention as years before 1950 CE) and to southern Africa by ~1500 BP, thereby spreading the largest single ancestry component to African genomes today (Russell et al, 2014; Tishkoff et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…6E) populations are successively removed from the list of donors. Nevertheless, the fact that Angola still represents a better proxy for the ancestry of southeastern Bantu speakers than populations closer to the Bantu homeland provides additional evidence in favor of a "late-split" between southwestern and southeastern Bantu-speaking groups after a single passage through the rainforest, as suggested in previous studies (20,21).…”
Section: East African Non-bantumentioning
confidence: 56%
“…Some interpretations of the archaeological data have proposed that, in contrast with the "late split" between East and West Bantu suggested by linguistic evidence, East Bantu peoples introduced the Urewe tradition into the Great Lakes by migrating out of the proto-Bantu heartland along the northern fringes of the rainforest after an early separation from Bantu speakers occupying the western half of Africa (18,19). This model, however, is not supported by recent genetic studies showing that Bantu-speaking populations from eastern and southern Africa are more closely related to West Bantu speakers that migrated to the south of the rainforest than they are to West Bantu speakers that remained in the north (20)(21)(22).…”
Section: Introductionmentioning
confidence: 76%
“…Overall, both mtDNA and ADMIXTURE studies suggested a diverse and admixed background of Egyptians sharing genetic signature and metabolic phenotypes with other Mediterranean nations. Although largely debated, into-Africa migration hypothesis [75] [76,77] seems to be supported by our largely diverse mtDNA haplotype collection demonstrated by just nine random samples. Egypt standing at the crossroad of different continents could have served as a gateway that allowed circulating people from Eurasia towards Africa since at least Holoscene [75]and lead to admixtures in east and sub-Saharan Africa that were reported before [76,77] and in this case lead to shared genetic predisposition to complex diseases such as obesity.…”
Section: Discussionmentioning
confidence: 80%